ANALYSIS OF VILLAGE FINANCIAL MANAGEMENT AND BUDGET REPORTING BASED ON PSAP NO. 02 IN DELI SERDANG REGENCY - Malika Callista Lubis; Rahmat Daim Harahap; Muhammad Lathief Ilhamy Nasution (JAT : Journal Of Accounting and Tax, 2026)
Abstract This study aims to analyze the compliance of village financial reporting with Government Accounting Standards Statement (PSAP) No. 02 on Budget Implementation Reports (LRA), evaluate the implementation of the Village Financial System (Siskeudes), and identify the supporting and inhibiting factors affecting village financial management in Percut Sei Tuan Subdistrict, Deli Serdang Regency. A qualitative approach was employed using primary and secondary data. Primary data were collected through interviews with village officials, while secondary data included Budget Implementation Reports (LRA), Village Budget Plans (APBDes), and relevant regulations. Compliance was assessed using a scoring method based on PSAP No. 02 indicators, including report structure, completeness, recognition and measurement of transactions, and presentation of SiLPA/SiKPA. The findings reveal varying levels of compliance among villages. Bandar Khalipah Village achieved the highest compliance rate (100%), followed by Kolam Village (66.67%) and Sumber Rejo Timur Village (55.56%). Although all villages have implemented Siskeudes, the effectiveness of its use depends on the competence of village officials in operating the system and understanding government accounting standards. Higher compliance levels are associated with better transparency and accountability. Supporting factors include the use of Siskeudes, training, and government assistance, while limited human resource capacity remains the primary challenge. Continuous training and technical assistance are essential to improve the quality of village financial reporting.